The chronicles of Fernão Lopes. - Lopes, Fernão, approximately 1380- (Textos B, 2023)
Volume III of the first complete English translation of the chronicles of Fernão Lopes chronicles the War of Succession (1383-1385), the rise of the House of Avis under João I, and his acclamation by the Cortes in Coimbra.